Role of nitric oxide in the in vitro splanchnic vascular hyporeactivity in ascitic cirrhotic rats - Cornel Sieber; Juan Carlos Lopez‐Talavera; Roberto J. Groszmann (1993)
The locally acting vasodilator nitric oxide has recently been implicated as a possible mediator in the vasodilatation observed in prehepatic portal hypertension. The aim of this study was to assess if nitric oxide could also be implicated in the vasodilation observed in experimental cirrhosis.In an in vitro preparation, the vascular responsiveness to potassium chloride of Krebs'-perfused superior mesenteric arterial vascular beds of control (n = 12) and cirrhotic (n = 10) rats with ascites, induced by CCl4, were tested.Increases in perfusion pressures over baseline in response to potassium chloride (125 mmol/L) were significantly lower in vessel preparations of cirrhotic rats (84.7 +/- 12.3 and 134.2 +/- 16.3 mmHg for cirrhotic and control rats, respectively, P < 0.05). This hyporeactivity was overcome by incubating the same vessel preparations with the stereospecific nitric oxide biosynthesis antagonist N omega-nitro-L-arginine (10(-4) mol/L). The corresponding increases in perfusion pressures were 145.1 +/- 18.0 and 173.0 +/- 14.8 mm Hg for cirrhotic and control rats, respectively (P = NS). Nitric oxide formation blockade increased the vascular response to KCl in cirrhotic and control rats, the respective percentage changes being 84.6% +/- 14.8% and 38.5% +/- 12.1% (P < 0.05).(1) Superior mesenteric arterial vascular beds of cirrhotic rats express a significant contracting hyporeactivity to KCl and (2) nitric oxide at least partly mediates the hyporesponsiveness in this in vitro preparation.